Ensuring That Dual-Use Means Multi-Value: A Framework for the Co-Prioritization of Cattle Grazing and PV Energy Generation - Nick de Vries; Anna Clare Monlezun (AgriVoltaics Conference Proceedings)
Photovoltaics (PV) is the fastest growing portion of the energy sector and the lowest-cost form of renewable energy today. PV development will continue to accelerate as the world strives to meet climate goals and reduce dependence on fossil fuels. The need for open, sun-abundant landscapes puts the solar (PV) industry in competition for land with agriculture and threatens intact native rangeland, stimulating valid concerns about negative impacts to ecological processes and function, such as soil stability, nutrient cycling, water cycling, and biodiversity. The co-location of PV energy generation and agriculture, commonly referred to as agrivoltaics, and specifically livestock grazing, offers a win-win scenario. While sheep grazing is being broadly employed, there is increasing interest in cattle grazing on PV projects. Our research seeks to understand if we can co-optimize cattle grazing and PV energy generation by designing and managing Solar Savannas, where ecological processes, capture of solar energy, and animal health and agricultural performance are equally prioritized. This is not only a question of dual-use but of multi-value. For agrivoltaics to be a meaningful sustainability solution, we hypothesize that dual-use must provide multiple values, including ecosystem service provision, agricultural production, and PV energy generation, bolstering community relationships and social and economic viability. We are engaged in ongoing research to ensure and measure this multi-value system, building ecological, agricultural, and financial models. What we learn from the modeling of this multi-value approach to eco-agri-energy systems is intended to eliminate tradeoffs of either-or systems, reduce barriers to dual-use systems, and finally, promote holistic solutions for the integration of multi-value systems. The purpose of this paper is to present a novel foundational framework, the Solar Savanna, and establish a theoretical basis for research and agrivoltaics practices.